Current status of glucosamine and chondroitin therapy in osteoarthritis (Medical Journal of Indonesia, 2005)
Osteoarthritis (OA) is the most common form of arthritis. Radiographic and or pathologic changes of OA are present in most people older than 65 years old. The management of OA is divided into medical / non surgical and surgical treatment. The medical treatment consisted of pharmacologic and non pharmacologic treatment. The pharmacologic treatment of OA is still problematic for many patients, either due to a lack of efficacy or due to the toxicity of the drugs used in the treatment of OA, so that many OA patients seek for alternative medication. Glucosamine and chondroitin are the most commonly used alternative agents for the treatment in OA. Many studies had been conducted to evaluate the efficacy of glucosamine and chondroitin in the treatment of OA. So far the result is controversial. The purpose of this article is to highlight the current status of the use of glucosamine and chondroitin in OA treatment. (Med J Indones 2005; 14: 55-8) Keywords: Osteoarthritis, Glucosamine, Chondroitin